Cross-border telework and the applicable labour law : The role of different connecting factors in determining objectively applicable law - Rosin, Annika (Sage, 2025)
In the case of cross-border employment, the applicable law is determined mainly according to habitual place of work. If this factor cannot be clarified, the engaging place of business of the employer determines the applicable law. Both factors can be set aside if the relationship is more closely connected to some other country.Telework is performed outside the employers’ premises, and the determination of the exact workplace can be difficult. This again complicates the determination of the applicable law in cross-border cases. This article analyses how, in the case of cross-border telework, the applicable law should be determined.It is argued that the exact system depends on the type of telework. If telework is performed in one country abroad, the habitual place of work determines the applicable law. If teleworker has at least two offices or manages his own working time, the second connecting factor applies. As the determination of the applicable law according to the engaging place of business is not considered to be sufficiently employee-protective, escape clause should be emphasised in the second case to guarantee the best employment protection to the employee.